An Innovative Australian Outreach Model of Diabetic Retinopathy Screening in Remote Communities - Nicola M. Glasson; Lisa J. Crossland; Sarah L. Larkins (Journal of Diabetes Research)
Background. Up to 98% of visual loss secondary to diabetic retinopathy (DR) can be prevented with early detection and treatment. Despite this, less than 50% of Australian and American diabetics receive appropriate screening. Diabetic patients living in rural and remote communities are further disadvantaged by limited access to ophthalmology services. Research Design and Methods. DR screening using a nonmydriatic fundal camera was performed as part of a multidisciplinary diabetes service already visiting remote communities. Images were onforwarded to a distant general practitioner who identified and graded retinopathy, with screen-positive patients referred to ophthalmology. This retrospective, descriptive study aims to compare the proportion of remote diabetic patients receiving appropriate DR screening prior to and following implementation of the service. Results. Of the 141 patients in 11 communities who underwent DR screening, 16.3% had received appropriate DR screening prior to the implementation of the service. In addition, 36.2% of patients had never been screened. Following the introduction of the service, 66.3% of patients underwent appropriate DR screening (p=0.00025). Conclusion. This innovative model has greatly improved accessibility to DR screening in remote communities, thereby reducing preventable blindness. It provides a holistic, locally appropriate diabetes service and utilises existing infrastructure and health workforce more efficiently.